Electrochemical Friedel–Crafts-type amidomethylation of arenes by a novel electrochemical oxidation system using a quasi-divided cell and trialkylammonium tetrafluoroborate - Senboku, Hisanori; Hayama, Mizuki; Matsuno, Hidetoshi (Beilstein Journal of Organic Chemistry, 2022)
Electrochemical Friedel–Crafts-type amidomethylation was successfully carried out by a novel electrochemical oxidation system using a quasi-divided cell and trialkylammonium tetrafluoroborates, such as iPr2NHEtBF4. Constant current electrolysis of 1,3,5-trimethoxybenzene or indoles in DMA containing 0.1 M iPr2NHEtBF4 using an undivided cell equipped with a Pt plate cathode and a Pt wire anode (a quasi-divided cell) resulted in selective formation of N-acyliminium ions of DMA at the anode, which reacted with arenes to give the corresponding amidomethylated products in good to high yields.
Keywords: electrochemical oxidation; Friedel–Crafts type amidomethylation; N-acyliminium ion; quasi-divided cell; trialkylammonium salt

(untitled) - Wu, P.; Nielsen, T. E. (Chem. Rev., 2017)

(untitled) - Yazici, A.; Pyne, S. G. (Synthesis, 2009)

(untitled) - Yazici, A.; Pyne, S. G. (Synthesis, 2009)

(untitled) - Maryanoff, B. E.; Zhang, H.-C.; Cohen, J. H.; Turchi, I. J.; Maryanoff, C. A. (Chem. Rev., 2004)

Advances in Heterocyclic Chemistry - Mazurkiewicz, R.; Październiok-Holewa, A.; Adamek, J.; Zielińska, K. (α-Amidoalkylating Agents: Structure, Synthesis, Reactivity and Application, 2014)

(untitled) - Graham, T. J. A.; Shields, J. D.; Doyle, A. G. (Chem. Sci., 2011)

(untitled) - Boiaryna, L.; El Mkaddem, M. K.; Taillier, C.; Dalla, V.; Othman, M. (Chem. – Eur. J., 2012)

(untitled) - Ryder, G. M.; Wille, U.; Willis, A. C.; Pyne, S. G. (Org. Biomol. Chem., 2019)

(untitled) - Ikeda, K.; Morimoto, T.; Sekiya, M. (Chem. Pharm. Bull., 1980)

(untitled) - Nakamura, K.; Togo, H. (Eur. J. Org. Chem., 2020)

(untitled) - Doan, S. H.; Nguyen, K. D.; Huynh, P. T.; Nguyen, T. T.; Phan, N. T. S. (J. Mol. Catal. A: Chem., 2016)

(untitled) - Shirakawa, E.; Uchiyama, N.; Hayashi, T. (J. Org. Chem., 2011)

(untitled) - Zhang, Y.; Teuscher, K. B.; Ji, H. (Chem. Sci., 2016)

(untitled) - Dai, C.; Meschini, F.; Narayanam, J. M. R.; Stephenson, C. R. J. (J. Org. Chem., 2012)

(untitled) - Kaur, J.; Shahin, A.; Barham, J. P. (Org. Lett., 2021)

(untitled) - Shono, T.; Matsumura, Y.; Tsubata, K. (J. Am. Chem. Soc., 1981)

(untitled) - Jones, A. M.; Banks, C. E. (Beilstein J. Org. Chem., 2014)

(untitled) - Jones, A. M. (Chem. Rec., 2021)

(untitled) - Yamamoto, K.; Kuriyama, M.; Onomura, O. (Chem. Rec., 2021)

(untitled) - Geske, L.; Sato, E.; Opatz, T. (Synthesis, 2020)

(untitled) - Yoshida, J.-i.; Shimizu, A.; Hayashi, R. (Chem. Rev., 2018)

(untitled) - Suga, S.; Nagaki, A.; Yoshida, J.-i. (Chem. Commun., 2003)

(untitled) - Nagaki, A.; Togai, M.; Suga, S.; Aoki, N.; Mae, K.; Yoshida, J.-i. (J. Am. Chem. Soc., 2005)

(untitled) - Wermeckes, B.; Beck, F. (Electrochim. Acta, 1985)

(untitled) - Danielmeier, K.; Schierle, K.; Steckhan, E. (Tetrahedron, 1996)

(untitled) - Hilt, G. (Angew. Chem., Int. Ed., 2003)

(untitled) - Gong, M.; Huang, J.-M. (Chem. – Eur. J., 2016)

(untitled) - Hilt, G. (ChemElectroChem, 2020)

(untitled) - Senboku, H.; Nagakura, K.; Fukuhara, T.; Hara, S. (Tetrahedron, 2015)

Organic Electrochemistry - Utley, J. H. P.; Nielsen, M. F. (Electrogenerated Bases, 2001)

Electroorganic Reduction Synthesis - Torii, S. (Electrogenerated Base-assisted Conversion, 2006)

Encyclopedia of Applied Electrochemistry - Kashimura, S.; Matsumoto, K. (Electrogenerated Base, 2014)

(untitled) - Frontana-Uribe, B. A.; Little, R. D.; Ibanez, J. G.; Palma, A.; Vasquez-Medrano, R. (Green Chem., 2010)

(untitled) - Kashimura, S. (J. Synth. Org. Chem., Jpn., 1985)

(untitled) - Uneyama, K.; Itano, N. (Denki Kagaku oyobi Kogyo Butsuri Kagaku, 1994)